The role of the retinoids in topical treatment of skin diseases - the review of the literature - Szczuraszek, Paulina; Szczuraszek, Hugo; Sałata, Piotr; Paluch, Michał; Tomkiewicz, Michał; Tomkiewicz, Julia; Żuchnik, Magda; Licak, Gabriela; Bętkowska, Paulina; Rybkowska, Agnieszka (Journal of Education, Health and Sport, 2023)
INTRODUCTION: Retinoids are a broad group of natural and synthetic compounds derived from vitamin A. Many studies have shown strong anti-aging effects, and they have also been shown to have therapeutic effects on acne vulgaris or psoriasis. Vitamin A and its derivatives make the skin more elastic and smooth, cause a decrease in fine wrinkles and cause an increase in fibroblast activity and collagen fiber production. Retinoid compounds regulate biological processes of the skin such as immune processes, angiogenesis, proliferation and differentiation. THE AIM OF STUDY: The purpose of this paper is to discuss the effects of retinoids and the use of the substances in skin diseases. MATERIALS AND METHOD: Literature review of PubMed, Google Scholar and Science Direct and evaluation of available randomized controlled trials using retinoids in terms of treatment effectiveness in terms of skin quality, anti-aging benefits use in dermatology. CONCLUSIONS: Vitamin A and its derivatives plays an important role in anty-aging prevention and treatment of skin diseases, such as acne vulgaris, psoriasis and photo-aging. There are still many ongoing studies and not known opportunities of its use to treat other skin diseases that we should be aware of and keep track of new papers that indicate such.